(untitled) (International Research in Economics and Finance, 2022)
Business process outsourcing (BPO) is a widely popular way that companies are conducting business all around the world. Employing such techniques can have a dramatic effect on your bottom line, but also open you up to many more advantages that ultimately help your business function more efficiently. The purpose of this report is to critically review past literature on the topic to gain a better understanding of why businesses will choose to outsource processes. This report will also seek to provide greater insights into the effects outsourcing has on the company and also the host country being outsourced. We found that there is an overwhelming trend to outsource processes from Australia and that brings other benefits such as getting closer to new market opportunities. The main body of this report outlines when and why a company should choose to outsource and the decision-making rationale around such concepts. Research also indicated that there is a booming industry for companies that assist in aiding the outsourcing process and connecting you with partners in various host nations. This report discovered that there are also some ethical and moral obligations that need to be carefully considered as recent criticisms have damaged the reputations of some businesses. Overall, the implications of our research hovered around a few key findings, the cost benefits associated with outsourcing and the greater efficiencies and quality in tasks that can be utilized in partnering with the right host company.